"The Most Harsh and Frank Gangster Picture We Have Ever Had": Censoring Howard Hawks's Scarface1. (2nd January 2020) - Alonge, Giaime
Abstract : Howard Hawks's Scarface (1932) was one of the most violent and controversial movies ever produced during the studio era. The film was finished in September 1931 but was released only in April 1932, because of a prolonged fight between the Hays Office and the production company, Howard Hughes's Caddo. This article not only reconstructs the relationship between Caddo and the Hollywood censors during the production of Scarface . On the basis of this historical evidence, it also addresses a question that has not been investigated yet: How did a movie that was so attentively – even obsessively – scrutinized by the Hays Office, which imposed numerous changes, still feature an incestuous passion between the protagonist and his sister? In an effort to answer this question, the article offers a broader hypothesis regarding the representation of criminals – especially Italian-American criminals – in classical Hollywood cinema.